Logotherapeutic management of persons with substance abuse/dependence (2009)
The paper examines the logotherapeutic management of persons with substance abuse/dependence which involves the utilization of a multi-disciplinary approach. Therefore, the paper highlights how this view is in relationship with the concept of logotherapy about man that comprises biological, psychological and spiritual dimensions which the management of substance abuse has to be based upon. Thus, efforts are made to describe logotherapy and logotherapeutic view of substance abuse/dependence. It is concluded with arguments on the need to include logotherapeutic approach to the management of persons with substance abuse / dependence.